Detection of Staphylococcus aureus’s Strain Similarity on Surgical Ward Nurses’s Hand and Nose and Post Operative Wound Infection Using Coa Gene Through PCR-RFLP Method - Fauzia Andrini; Imam Supardi; Sunarjati Sudigdoadi; Sadeli Masria (Jurnal Ilmu Kedokteran, 2010)
Staphylococcus aureus (S.aureus) remains to be the most important cause of post operative wound infection. Nursescould become reservoirs to transmit S.aureus through contaminated hands transiently, or through colonized nose.Strain polymorphism could be determined by Restriction Fragment Length Polymorphism (RFLP), using coa gene andrestriction endonuclease enzyme Alu1. There were 30 isolates of S.aureus’s infection, and 20 isolates taken from handsand nose of the nurses in charge. From 50 isolate positive S.aureus, PCR results showed single and multiple bandswithin 300 to 900 base pairs (bp) in length, and multiple bands within 200 to 600 bp. Five out of 30 patients (17%)showed no PCR-RFLP similarity with any of the nurses. Ten out of 15 nurses which hands were positive for S.aureus,has PCR-RFLP similarity with some patients. There was only 1 out of 5 nurses which nose was positive for S.aureus,showed PCR-RFLP similarity with some patients. Statistically, the proportion of the similar PCR-RFLP between thosesamples in this study is 0.12 (12%). Conclusion: Nurses had 12 % PCR-RFLP similarity for S.aureus with post operativewound infection.